Physical Characteristics and Utilization oft the Karst Beaches in Kabupaten Gunungkidul - Damayanti, Astrid; Ayuningtyas, Ranum (UI Scholars Hub, 2008)
Physical Characteristics and Utilization oft the Karst Beaches in Kabupaten Gunungkidul. Karsts beaches at Gunungkidul Regency (Baron, Kukup, Sepanjang, Drini, Krakal, Ngandong, and Sundak), located in south of Daerah Istimewa Yogyakarta Province, have economic potential. Even they have similarity in geological condition (genesis and morphological processes), but they have different physical characteristics. Based on result of observation environment on morphological conditions and spatial analysis method, we found the proper utilization of the beaches.